115. Feasibility study for In-Vivo Dosimetry procedure in routine clinical practice. (December 2018) - Falco, M.D.; Giancaterino, S.; De Nicola, A.; Adorante, N.; De Lorenzo, R. Gimenez; Di Tommaso, M.; Vinciguerra, A.; Trignani, M.; Allajbej, A.; Greco, F.; Grusio, M.; Genovesi, D.; et al.
Abstract : Purpose: To present In-Vivo Dosimetry (IVD) results obtained elaborating EPID images by a commercial software. Methods: 8474 IVD tests for 386 cancer patients treated with 3DCRT, IMRT and VMAT techniques, were performed using the SOFTDISO software. SOFTDISO uses EPID-images to calculate for each beam (i) the R index, i.e. the ratio between daily reconstructed dose and the planned one at isocenter point and (ii) a γ -like analysis between the reference EPID image and that obtained in a daily fraction. γ -like analysis supplies two indexes: the percentage of points with γ < 1 ( γ % ) and the mean γ value, ( γ mean ) . For each test, the pass criteria for the signals (S) agreement Δ S% and distance to agreement Δ d, were: 0.95 ⩽ R ⩽ 1.05, γ % ⩾ 90% and γ mean ⩽ 0.5. Results: The results of R ratios, the γ -like analysis and the visual inspection of out of tolerance tests, together with the patient anatomical images, permitted to individuate 2 classes of errors: class-1, due to inadequate standard quality controls and class-2, due to patient morphological changes. Depending on the technique and anatomical site, a maximum of 18% of tests had at least one index out of tolerance level (OTL). Once removed the causes of class-1 errors, all patients (except four lung and two breast cancer patients treated with 3DCRT) presented mean indexes values ( R ¯, γ ¯ % and γ ¯ mean ) within tolerance at the end of treatment course. Class-2 errors were found in some patients. As an example, the Table reports the results of 1810 tests for prostate and H&N tumours treated with VMAT technique with 163 OTL tests (9%). As regards the workload, it took 20 min for 10 patients per day. Conclusions: The IVD procedure with SOFTDISO resulted easily implementable and able to individuate errors with a limited workload.